Diversity and abundance of polyisoprenoid composition in coastal plant species from North Sumatra, Indonesia - MOHAMMAD BASYUNI; RIDHA WATI; HIROSHI SAGAMI; SUMARDI SUMARDI; SHIGEYUKI BABA; HIROSUKE OKU (Biodiversitas Journal of Biological Diversity, 2018)
Basyuni M, Wati R, Sagami H, Sumardi, Baba S, Oku H. 2018. Diversity and abundance of polyisoprenoid composition in plant species from North Sumatra, Indonesia. Biodiversitas 19: 1-11. The distribution and abundance of polyprenols (pol) and dolichols (dol) in the leaves and roots of fourteen coastal plants from North Sumatra, Indonesia were analysed using two-dimensional thin layer chromatography. In the leaves, with respect to the distribution of pol and dol were detected and categorized into three-types. In type-I, the predominance of dol over pol, was observed in Barringtonia asiatica, Calophyllum inophyllum, Pandanus odoratissimus, and Stachytarpheta jamaicensis. In type-II, the presence of both pol and dol, was observed in Casuarina equisetifolia, Melastoma candidum, Morinda citrifolia, Scyphiphora hydrophyllacea, Sesuvium portulacastrum and Terminalia catappa. In type-III, the predominance of pol over dol, was observed in Acacia auriculiformis, Hibiscus tiliaceus, Ricinus communis, and Pongamia pinnata. However, in the roots, a type-I distribution was observed in eleven species, while three species, A. auriculiformis, M. candidum, and M. citrifolia, corresponded to a type-II distribution instead of type-III. The diversity of polyisoprenoid composition in the leaves was noted, whereas 79% of root tissues indicated that dol occur more abundantly than pol. The range of the contents of polysioprenoid was 12-300 mg/g dw. The present study indicated that pol and dol could be useful in the classification of mangroves and other coastal forests and in phylogenetic studies. The diversity and presence of polyisoprenoids in coastal plants suggested that plant polyisoprenoids are chemotaxonomically important.